Integrating Declarative and Procedural Knowledge on Grammar through E- Portfolio Assessment - Rukminingsih Rukminingsih (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2020)
This study aims to reveal (1) whether there is significance different students’ achievement who are taught grammar through integrating declarative and procedural knowledge by implementing E-Portfolio assessment and (2) the process of integrating declarative and procedural knowledge by implementing E-Portfolio assessment. It employed mixed method of concurrent design.The population of this research was 120 students of grammar class in English Department of STKIP PGRI Jombang. The number of sample was 40 students for experimental group and 40 students for control group by employing cluster random sampling technique. The data was collected through test and observation and it applied ANCOVA for quantitative data analysis and data display, data reduction and drawing conclusion for qualitative data analysis. The finding showed that (1) there is significant difference on students’ grammar understanding between experimental group and control group. (2) E portfolio through students’ blogs gives opportunity to students to engage their efforts, progress, and achievements in given areas and the strategy has the additional benefit of enabling students to publish and share ideasor tasks easily involving authentic audience or their classmates.It implied that assessing by using Electronic Portfolio is positively effective to be implemented in integrating both declarative and procedural knowledge in Grammar course.